The Role of IL-6 in Cancer Cell Invasiveness and Metastasis—Overview and Therapeutic Opportunities - Magdalena Rašková; Lukáš Lacina; Zdeněk Kejík; Anna Venhauerová; Markéta Skaličková; Michal Kolář; Milan Jakubek; Daniel Rosel; Karel Smetana; Jan Brábek (Cells, 2022)
Interleukin 6 (IL-6) belongs to a broad class of cytokines involved in the regulation of various homeostatic and pathological processes. These activities range from regulating embryonic development, wound healing and ageing, inflammation, and immunity, including COVID-19. In this review, we summarise the role of IL-6 signalling pathways in cancer biology, with particular emphasis on cancer cell invasiveness and metastasis formation. Targeting principal components of IL-6 signalling (e.g., IL-6Rs, gp130, STAT3, NF-κB) is an intensively studied approach in preclinical cancer research. It is of significant translational potential; numerous studies strongly imply the remarkable potential of IL-6 signalling inhibitors, especially in metastasis suppression.